The Complete Mitochondrial Genome of Lepidotrigona flavibasis (Hymenoptera: Meliponini) and High Gene Rearrangement in Lepidotrigona Mitogenomes. Issue 3 (3rd June 2021) - Wang, Cheng-Ye; Zhao, Min; Wang, Shi-Jie; Xu, Huan-Li; Yang, Ye-Meng; Liu, Li-Ning; Feng, Ying
Abstract: We reported the sequence and characteristics of the complete mitochondrial genome of an ecologically important stingless bee, Lepidotrigona flavibasis (Hymenoptera: Meliponini), that has suffered serious population declines in recent years. A phylogenetic analysis based on complete mitogenomes indicated that L. flavibasis was first clustered with another Lepidotrigona species ( L. terminata ) and then joined with the other two Melipona (Hymenoptera: Meliponini) stingless bees ( M. scutellaris and M. bicolor ), forming a single clade of stingless bees. The stingless bee clade has a closer relationship with bumblebees ( Bombus ) (Hymenoptera: Apidae) than with honeybees ( Apis ) (Hymenoptera: Apidae). Extremely high gene rearrangements involving tRNAs, rRNAs, D-loop regions, and protein-coding genes were observed in the Lepidotrigona mitogenomes, suggesting an overactive evolutionary status in Lepidotrigona species. These mitogenomic organization variations could provide a good system with which to understand the evolutionary history of Meliponini.